2017
DOI: 10.1101/201293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular diversity of the somatosensory cortical map plasticity

Abstract: Sensory maps are representations of the sensory epithelia in the brain. Despite the intuitive explanatory power behind sensory maps as being neuronal precursors to sensory perception, and sensory cortical plasticity as a neural correlate of perceptual learning, molecular mechanisms that regulate map plasticity are not well understood. Here we perform a meta-analysis of transcriptional and translational changes during altered whisker use to nominate the major molecular correlates of experience-dependent map pla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 221 publications
(282 reference statements)
0
8
0
Order By: Relevance
“…Experience-dependent cortical plasticity studies revealed multiple critical periods. More recent studies are expanding the concept of critical periods and barrel cortex plasticity to cellular and molecular levels involving neurons, glia, and endothelial cells (and adaptive changes at the molecular levels) (Kole et al, 2018).…”
Section: Critical-period Plasticitymentioning
confidence: 99%
“…Experience-dependent cortical plasticity studies revealed multiple critical periods. More recent studies are expanding the concept of critical periods and barrel cortex plasticity to cellular and molecular levels involving neurons, glia, and endothelial cells (and adaptive changes at the molecular levels) (Kole et al, 2018).…”
Section: Critical-period Plasticitymentioning
confidence: 99%
“…Combined with the systematic molecular, structural and functional reconstruction (see e.g. (Meyer et al, 2010(Meyer et al, , 2013Narayanan et al, 2015;Huang et al, 2016;Kole et al, 2017bKole et al, , 2017aKole et al, , 2018da Silva Lantyer et al, 2018;Kole and Celikel, 2019)) of the these circuits, a comprehensive multi-scale computational map of sensorimotor computation is evolving.…”
Section: Discussionmentioning
confidence: 99%
“…For electrochemical measurements of neurotransmitters, quartz capillaries were heated for 60 s, dipped in CNTs dispersed in Nafion solution (5 mg mL -1 in ethanol). Electrochemical measurements were carried in artificial cerebrospinal fluid (aCSF) as described before (Kole, 2015;Kole et al, 2017bKole et al, , 2017aKole et al, , 2018 and included 135mM NaCl, 5.4mM KCl, 5mM Na-HEPES buffer, 1.8mM CaCl 2 and 1mM of MgCl 2 .…”
Section: Electrochemical Setupmentioning
confidence: 99%